Kedudukan dan Hak-Hak Perempuan Dalam Perspektif Islam - Wilda Rahma Nasution (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Women are beings created by Allah Swt., just as men with perfect form because they are equipped with reason and conscience. However, in the course of his life, there were controversies and problems. The position and rights of women are still questioned and debated in contrast to men who are seen as perfect human beings with no flaws. These differences give birth to injustices that impact women which manifest in various forms such as marginalization, subordination, stereotypes, and workload. The method used is a qualitative method where researchers follow a theoretical orientation with the type of literature research, the data obtained are extracted from various literature related to research. The analysis in this paper shows that women have the same position as men, both as servants of Allah Almighty and caliphs on earth. But that does not mean women are given the same position and rights as men. To maintain the chastity, position, and dignity of women, Islam guides with the provisions of Islamic law as limits and protections, not as discrimination or injustice of women's position and rights.